Diaspora Digitalized in Michelle De Kretser’s 'Questions of Travel' and Kiran Desai’s 'The Inheritance of Loss' - Khadka, Uwaraj (JMC Research Journal, 2020)
The research work explores the diasporic aspect of immigrants’ lives while living on the digital platform. Then, it attempts to investigate how digital technologies have assisted diasporic individuals to consider their new acquired time and space as comfort zone. All Diasporas in today’s world live in the transnational location which makes them get connected digitally with their roots at the same time. So, diasporic individuals are supported and assisted by the digital technologies. The more the immigrants make use of these technologies while living in the transnational location the more they go global and at the same time get connected with the local. To demonstrate this argument, the research examines and analyzes Kiran Desai’s novel “The Inheritance of Loss” and Michelle de Kretser’s novel “Questions of Travel” in order to show how immigrants being assisted by the digital technologies, despite the cultural wilderness and oddities encountered in the alien lands, celebrate their comfort zone, and live on the transnational location. The analysis part is reached through by referring to the works on identity; digital technologies, nationalism and trans-nationalism that help assess validity of the argument proposed herein.